Iridium-Catalyzed Anti-Stereoselective Ring-Opening Reactions of Azabicyclic Alkenes with Fluoroalkylamines - Yang, Wen; Cheng, Guo; Li, Yue; Zuo, Xiongjun; Yang, Dingqiao (Synthesis, 2017)
A novel iridium-catalyzed ring-opening reaction of azabicyclic alkenes with a variety of fluoroalkylamines was developed. The reaction gave a series of fluorinated trans-1,2-diamine derivatives in good to excellent yields (up to 98%) under relatively mild conditions. The effects of various ligands, catalyst loading, solvents, and temperatures on the yield of the reaction were also investigated. This is the first time that fluorinated compounds were synthesized by incorporating a series of fluoroalkylamines into hydronaphthalene skeleton.
Keywords: iridium catalyst; fluoroalkylamines; azabicyclic alkenes; ring-opening reaction; fluorinated trans-1,2-diamines